Św. Hieronim, Prolog do Księgi Jozuego - Krzyszczuk, Łukasz; Poznański, Adam (Vox Patrum, 2025)
Around the year 390, St Jerome abandoned his work on translating the Greek Septuagint into Latin and began rendering the Old Testament – as he repeatedly claims – directly from the Hebrew. His own statements make it abundantly clear that in this translational endeavour he is guided by the principle of the Hebraica veritas (“Hebrew truth”), and that he refers to the Hebrew original rather than to the Greek Hexaplaric versions based on the Hebrew Bible. Jerome thus departs from the Septuagint in favour of the meaning conveyed by the Hebrew text known in his time. As he himself affirms, he is able to do so thanks to his knowledge of Hebrew and with reference to the Hebrew source text, on which his Latin translation of the Old Testament is based. After the death of Paula of Rome, his close companion, Jerome of Stridon translated the books of Joshua, Judges, and Ruth – a task he undertook around 404/405, toward the end of his work on the Hebrew Bible. The present article offers a translation of a short text which the Bethlehem monk attached to his Latin version of the last three books of the Octateuch, and which has come down to us under the title Praefatio in libro Iosue. The translation is preceded by an introduction that outlines the interpretative issues encountered in reading this opusculum by Jerome, as well as by a description of the manuscript fragment containing the oldest extant copy of the text preserved in Polish collections.